Renal hilar pheochromocytoma with nonfunctional kidney - Amit Tuli; Navroop Kaur; Kim J Mammen (Wolters Kluwer Medknow Publications, 2018)
Pheochromocytomas are neuroendocrine tumors derived from embryonic neural crest cells. They are mostly found in the adrenal glands (pheochromocytomas) and sometimes in the extra-adrenal paraganglia (paragangliomas) of the autonomic nervous system. Paragangliomas arising from the kidney or in the renal hilus are very rare, and preoperative diagnosis is rarely made.We present the case of a 38-year-old hypertensive female, presenting with dull aching, nonradiating right flank pain for 2 months and no other symptoms. Computed tomography demonstrated a well-defined, hypodense enhanced lesion located on the hilum of the right kidney. Laparotomy was performed, and histology of the excised mass revealed an extra-adrenal pheochromocytoma. The intervention was effective, and the patient is doing fine.